Jagad Raya: Representation of Flora and Fauna in Wooden Craft From A Cosmological Perspective - Eko Haryanto; Mujiyono Mujiyono; Nadia Sigi Prameswari (Universitas Negeri Medan, 2023)
The art of teak wood carving was one of the leading export commodities, especially wood carvings with flora and fauna motifs. Javanese culture and Hindu mythology influenced the flora and fauna motifs, so they had their meanings. This research aimed to develop carvings of flora and fauna motifs inspired by classic batik motifs using wood media. The results showed that the media used was teak wood with a finishing process without painting to produce a natural color. It was adjusted to its function and use in creating teak wood carvings. Wood carving did not only function to be enjoyed for its aesthetic value but as a decorative and sacred medium where each motif influences one's beliefs when creating artwork. In addition, teak wood carvings were used as symbols of a culture, and the designed motifs often contained the meaning of teachings to humans in carrying out life. Based on the economic aspect, the teak woodcarving industry strategically improved the community's income, especially for craftsmen in tourism centers. By making woodcarving crafts with flora and fauna motifs, it hoped that woodcarving crafts would not only use as decorative objects, but it used as an educational media for fine art, history, and Javanese culture, which were full of meaning to the broader community so that they could increase knowledge and encourage people to behave following the concept of cosmology.